Traditional arts in Southern Arabia : music and society in Sohar, Sultanate of Oman. - Christensen, Dieter (Intercultural music studies, 2009)
The Arabian Peninsula, and in particular, the coastal areas of the Arab Gulf, the Gulf of Oman and the Arab Sea, boast since times immemorial a wealth of cultural forms to which the people of the desert and those of the sea and from across the seas have amply contributed. The arts—music, dance, poetry in performance—not only testify to a deep history and express diverse ethnic identities; as an integral part of daily life they are also instrumental in balancing multicultural society and adapting local communities to the effects of national and global modernization. The authors have studied, during several residences between 1985 and 2006, the state and evolution of performance practices and the social roles of performed arts in Sohar, an ancient and still important coastal town of the Sultanate of Oman. The book situates and describes the arts (al-fun¯un) and their practitioners in the province and town of Sohar, studies the underlying concepts and the social networks through which the arts exist, and analyses the forces of change that have affected the arts as part of society in Sohar -- Présentation de l'éditeur.